Pengembangan Instrumen Penilaian Kognitif Berbasis Google Form Pelajaran Matematika - Iwan Hariono; Iskandar Wiryokusumo; Achmad Noor Fathirul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
The guide in the form of a cognitive assessment instrument based on Google form a Class V mathematics lesson resulted from this development research. During the mathematical assessment activities, most educators are still using the old way with paper-based assessment systems. While the demands of parents and learners want a practical, fast, and efficient assessment but still pay attention to the correct assessment procedures that are online-based assessments by utilizing Google forms. Model ADDIE (analysis, design, development, implementation, and evaluation) used in the study. The types of data used in this study are the results of media expert validation, material experts, and small group trials. Validation of material members amounted to 85%, media expert validation of 93%, small group response to the practice of a Google form-based math problem of 81%. Thus it can be concluded that this development product can be used as a reference because the interpretation reaches the criteria is very feasible so that this product can be implemented